Pengaruh Latihan Plyometric Barrier Hops, Front Cone Hops, Jump To Box, dan Depth Jumps terhadap Peningkatan Power, Kekuatan, dan Kecepatan Siswa Ekstrakulikuler - Haromain, Imam; Wiriawan, Oce; Arief, Nur Ahmad; Hidayat, Taufiq; Wibowo, Sapto; Siantoro, Gigih; Wahyudi, Achmad Rizanul (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2024)
This research aims to determine the effect of Plyometric Barrier Hops, Front Cone Hops, Jump to Box, and Depth Jumps training on increasing the power, strength and speed of extracurricular students at SMA Muhammadiyah 10 Surabaya. This research is experimental research and the instruments in this research use Jump MD to measure power, Leg Dynamometer to measure strength, and 30 meter Sprint to measure speed. The results of this research show that plyometric training of barrier hops, front cone hops, jump to box, and depth jump can significantly increase power, strength, and speed due to sig. < 0.05. This data has significant potential for practitioners in identifying potential weaknesses and improving training methods for athletes who rely heavily on the initiation elements of power, strength, and speed.